MINAT MENGGUNAKAN MOBILE BANKING PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BRAWIJAYA UNTUK MELAKUKAN TRANSAKSI PEMBAYARAN SPP - Wibowo, Anggriawan Setyo (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research has a purpose to examine the factors which affect individual intention to use mobile banking. The factors which affect individual intention to use mobile banking in this research are perceived usefulness, perceived ease to use, anxiety, trust,Â  subjective norm, and perceived behavioral control. This research is a development of previous research that uses a combination of TAM, and TRAÂ  models. Data collection method used is surveymethod.Sample in this research are accountance student University of Brawijaya Malang.The data were analyzed by using Partial Least Square (PLS). The result showed that anxiety and subjective norm affect an individual intention to use mobile banking. Otherwise, the construct of perceived usefulness, perceived ease of use, trust, and perceived behavioral control do not affect individual intention to use mobile banking. The implications of this research are relevant for banking institutions to consider the factors which influence an individual intention to use mobile banking in the development the information systems. Keywords: Mobile banking, Trust, Perceived Usefulness, Perceived Ease of Use, Attitude Toward Use, Behavioral Intention, TAM, TRA.